Tuja Shuttle Run Improves Speed and Agility in Male Futsal Athletes in Magetan Regency: The Role of Body Mass Index Characteristics of Athletes - Fitri Avita Sari, Tutur Jatmiko, Abdul Hafidz, Kunjung Ashadi, Roestam Effendi Sijar, Haryo Mukti Wi (Lembaga Bale Literasi, 2025)
This study aims to analyze the effect of Tuja Shuttle Run training on improving the speed and agility of male futsal athletes in Magetan Regency and to examine the role of Body Mass Index (BMI) characteristics in supporting physical performance. This study used a quantitative approach with a quasi-experimental method through a one-group pretest-posttest design. There were 20 subjects selected purposively based on the criteria of active training and no injuries. The instruments used included BMI measurement, a 20-meter sprint test for speed, a Multistage Fitness Test to estimate VO?max, and an Illinois Agility Test for agility. The Tuja Shuttle Run training program was carried out in a structured manner for several weeks with high intensity and a controlled rest ratio. The results showed a significant increase in speed and agility, as indicated by a decrease in test time, as well as changes in BMI that were more supportive of movement performance. The paired sample t-test showed a significance value of < 0.05 for all variables, so it can be concluded that the Tuja Shuttle Run training effectively improves the biomotor components of speed and agility and supports the anthropometric characteristics of futsal athletes.